The importance of modern technology in teaching the Arabic language - Benchehda, Khadjidja; Bouhraoua, Hebib; Zohra, Zenoud; Djamila, Benlakreder (The International tax journal, 2025)
The current era is witnessing technological developments that have imposed themselves on all areas of life, including education. Its objectives, methods, and approaches have changed, and new terms and labels have emerged for modern learning methods: e-learning, distance learning, and digital learning. All of these methods explore the use of digital technology in the teaching and learning process. Digital learning can be considered a new teaching method that delivers educational content and conveys skills and concepts to learners through information and communication technologies and their various media, enabling learners to actively interact with the content and the teacher. Therefore, one of the objectives of this chapter is to introduce digital technology, the most important modern means and media in education, and their importance in promoting Arabic language teaching.